MEMETAKAN AKTOR POLITIK LOKAL BANTEN PASCA ORDE BARU: Studi Kasus Kiai dan Jawara di Banten - ABDUL HAMID, ABDUL HAMID (Program Magister Ilmu Politik, Universitas Diponegoro, 2010)
AbstractThis study analyzed the role of cultural political actors in Banten: Kiai and Jawara. Thepolitical role of Kiai in Banten has risen and fell down. In 1945 until 1950, all of the Bupati in Bantenwere positioned by Kiai. Since that time to now, the leadership of Kiai has decreased. In New Orderera, many Kiais were organized as supported organization of ruling party. It was mutualism relation,ruling party got mass supports and Kiai got material support for himself and pesantren. Jawara arerural strongmen or semi socially embedded men of prowess who are skillful in pencak silat and someare believed to have magical power, called ilmu. Some Jawara has been organized by Golkar party,since 1972. In post-Soeharto era, jawara has been predominance power. They put their family inmany political positions both in executive and legislative. They use intimidation and violence to gettheir aim.On the other side, Kiai had been fragmented in many political powers, but still as supportingactor not as the main one. To fulfill their needs, both for their selves and for pesantren, some Kiaishas done pragmatically and depended on others. The mix of political and economic weakness madeKiai failed to be a main actor in banten local politics.Keywords: Local politics, Local political actors, Power